UUM targets 10pc lecturers with PhDs - Daily Express, (KK) (Daily Express (KK), 2012)
SINTOK: Universiti Utara Malaysia (UUM) is targeting to have 10 per cent of its 1,200 lecturers holding Doctor of Philosophy (PhD) degrees and be one of the world's top 100 universities by 2020.